Demographic and Clinical Profile of Tuberculous Mastitis Patients at Tebet General Hospital, Jakarta - Desak Ketut Nari Swari Pramegia; Rio Putratama Achmad Faried; Kelvin Setiawan; Bramastha Aires Rosadi; Terry Renata Lawanto (Program Studi Ilmu Bedah, Fakultas Kedokteran Universitas Udayana, 2019)
Aim: Objective of the study is to find out the demographic and clinical profile of tuberculous mastitis (TM) patients. Methods: The study was carried out for a period of one year from August 2017 to August 2018 at Tebet General Hospital. Histopathologically diagnosed cases of TM were retrospectively studied. Results: All eight patients diagnosed as suffering from TM were females with the mean age of 37.25 years. Of these, two patients were lactating, six others were not, and 75% were multiparous. Unilateral involvement was observed in all cases. The right breast was affected in 62.5% and left breast in 37.5% cases. Patients presented with a solitary lump on one breast (87.5%), swelling of the breast (37.5%), and breast pain (100%). In the present study, two of the patients had previous positive tuberculosis (TB) contact and more than half found to be below an average economic level. All the patients were negative on the HIV test; also, there was no focus of TB elsewhere in the body. Conclusion: Tuberculosis should be considered as one possible cause of either mastitis or breast abscess. Histopathology examination played an important role in the diagnosis of TM. Standardized sequence for the diagnosis of TM is needed to increase awareness of the disease.